Ecology and life history of the Vlei Rat, Otomys Irroratus (Brants, 1827), on the Van Riebeeck Nature Reserve, Pretoria - Nel, Jan A.J. (University of Pretoria, 2013)
Thesis (DSc)--University of Pretoria, 1973.